Familial Mediterranean Fever and Multiple Sclerosis Successfully Treated With Interferon Beta-1a: A Case Report - Bilgin ÖZTÜRK, (Archives of Rheumatology, 2019)
Multiple sclerosis (MS) is the most common demyelinating disease in Turkey while familial Mediterranean fever (FMF) is the most common periodic fever syndrome worldwide. In this article, we report a 37-year-old male patient admitted with complaint of difficulty in walking. He had been taking colchicine at admission for 27 years. Despite this therapy, he had been experiencing twice monthly severe FMF attacks. After systemic and neurological examinations, laboratory tests and cranial and spinal magnetic resonance imaging, he was diagnosed as MS. Interferon (IFN) beta-1a was initiated three times/weekly subcutaneously for MS treatment. He stopped colchicine treatment after five months of IFN treatment because he did not suffer from any FMF attacks. He is still attack free for both diseases for a follow-up duration of 12 months. IFN beta is one of the most preferred agents for MS treatment but not one of the agents used for the treatment of FMF. Interferon beta can be a treatment of choice in patients with coincident FMF and MS and can be used in colchicine-resistant patients after being studied in systematic clinical studies.